Feasibility Study Investment Analysis On Distribution Water Supply System Development Of Pdam Delta Tirta Sidoarjo From Marketing Aspect, Technical Aspect, And Financial Aspect - Atika Emma Wulandari; Endang Chumaidiyah; Sinta Aryani (eProceedings of Engineering, 2021)
Abstract PDAM Delta Tirta is a Regional Water Company that owned by Sidoarjo Goverment as a regional goverment. In running its business there are several obstacles that are experienced by PDAM Delta Tirta Sidoarjo. One of them is the lack of water distribution capacity for customers. Based on interviews with PDAM Delta Tirta Sidoarjo, PDAM Delta Tirta Sidoarjo plans to expand its business by doing an investment in water supply system development. Based on the problems and business development plan, an incremental feasibility analysis is carried out. The aspects that taking into consideration are market aspect, technical aspect and financial aspect. Based on feasibility analysis conducted shows that PDAM Delta Tirta’s business development plan is feasible to be done. This is because the NPV value of business development plan is Rp 134.832.836.204,79, IRR of 9.6% and PBP of 4,730 years. Meanwhile, based on the incremental feasibility calculation, the NPV value is Rp 82,176,572,724.92an IRR of 10.7%. In addition, the sensitivity analysis shows that PDAM Delta Tirta's business investment is sensitive to a decrease in selling price by 6.37% and a decrease in demand by 6.16%. Keywords